EXAMINATION OF THE VIEWS OF VOLUNTEERS PARTICIPATED IN AN INTERNATIONAL SPORTS ORGANIZATION - Hasan Ceyhun Can; Erdal Zorba (ümit doğan üstün, 2019)
The purpose of this study was to evaluate the opinions of volunteers who participated in an international sports organization. For this purpose, this study was designed with phenomenological pattern which is one of the qualitative research approaches. The sample group consisted of 19 volunteers who participated in the Volleyball Nations League (VNL) which was organized by Fédération Internationale de Volleyball in Ankara during 28-29-30 May 2019. Convenient sampling method was used to determine the sample group. The data was collected through semi-structured interview form evaluated with content analysis method. According to the results of the study it was found that a volunteer must be a social individual who has a sense of responsibility, analytical thinking skills, strong characteristic qualities, enthusiasm and strong communication skills. The study showed that volunteer candidates were mostly motivated to participate in organizations to further their careers. After a volunteering activity the individuals obtained most positive outcome in their personal relationships. Additionally, volunteers stated that they gained positive outcomes with regards to experience, self-confidence, personal growth, morale and sense of responsibility. However, the participants stated loss of time, stress, fatigue and sense of failure as possible negative outcomes.